Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $G$ be a finite group. A subgroup $H \le G$ is called permutable, if for each other subgroup $U \le G$ we have $UH = HU$. Show that if $H \le G$ is permutable, then $H$ must be subnormal.

Does anybody knows an elementary proof of this fact?

share|improve this question

2 Answers 2

up vote 3 down vote accepted

This should be completely elementary. I got the idea for this answer by looking in the book "Products of Finite Groups" (link to publisher page), pg. 12, Lemma 1.2.9. This might be a good reference for more material about permutable subgroups.

First, two small results.

(1) If $H$ is a subgroup of $G$ and $G = H^g H$, then $H = G$.

Proof: Now $g^{-1} \in H^g H = g^{-1}HgH$, so $1 \in HgH$ and thus $g \in H$.

(2) Suppose that $H \leq G$ is permutable. If $H \leq M$ for a maximal subgroup $M$, then $H \leq M^g$ for all $g \in G$.

Proof: If $H \not\leq M^g$, then $HM^g = M^gH = G$ since $H$ is permutable and $M^g$ is maximal. But this implies $G = M^gM$, which is a contradiction by (1).


Now for your result, proceed by induction on the order of $G$. Assume that $H$ is a proper permutable subgroup of $G$. Now $H$ is contained in a maximal subgroup $M$, and by (2) the subgroup $H$ is contained in the proper normal subgroup $\cap M^g$. Apply induction to $\cap M^g$ and we are done.

share|improve this answer

Assume the contrary and let $G$ be minimal counter example,

Let $N=H^G$, if $N$ is proper in $G $ by our assumtion $H$ is subnormal in $N$ and $N$ is normal in $G$ we are done.

So, assume $N=G$ ,

Let $M$ be a maximal subgroup containing $H$.

Since, $H^G=G$ there exist a $M^x$ such that $H$ is not contained in $M^x$.

We have $HM^x=G\implies MM^x=G$ which is impossible.

In Mikko's answer, it seems to be better explained.

share|improve this answer
    
why is $MM^x = G$ impossible? –  Stefan Jun 8 at 21:37
1  
@Stefan: You can see it in Mikko's answer (1), that is why I did not write it again, if $MM^x=G \implies M=G$. –  mesel Jun 8 at 21:44
    
@JackSchmidt: I noticed that I used quatient reduction to get $G=H^G$ so I changed my argument. –  mesel Jun 9 at 0:29
    
Looks good. :-) –  Jack Schmidt Jun 9 at 0:34
    
I think so :-). –  mesel Jun 9 at 0:37

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.